An Iron Porphyrin Complex with Pendant Pyridine Substituents Facilitates Electrocatalytic CO2 Reduction via Second Coordination Sphere Effects - Ramuglia, Anthony R.; Budhija, Vishal; Ly, Khoa H.; Marquardt, Michael; Schwalbe, Matthias; Weidinger, Inez M. (ChemCatChem, 2021)
A bispyridylamine-based hanging unit within the ligand framework of a newly synthesized iron porphyrin complex (Py2XPFe) can act, on the one hand, as a hydrogen bonding site to facilitate proton transfer in catalysis and, on the other hand, as coordination site for a second Lewis acidic metal center. The bispyridylamine group in close proximity of the iron porphyrin center is able to mediate electrocatalytic CO2 reduction in anhydrous MeCN. The hydrogen bonding interactions within the hanging group affect the kinetics of catalysis likely through stabilization of the [FeI(CO2H)]− intermediate, increasing the overall rate of catalysis when compared to the non-functionalized analog, TMPFe (TMP=tetramesitylporphyrin). The rate constants (kapp) of the reduction reaction were calculated using the FOWA method which resulted in a higher TOFmax for the complex Py2XPFe compared with TMPFe in neat MeCN (1.7×102 vs. 1.1×101 s−1). The addition of weak Brønsted acids to the reaction mixture (TFE or PhOH) shows an increase in the rate of catalysis for both complexes, yet the Py2XPFe analog displays higher TOFmax at each relative acid concentration, suggesting the hanging group beneficially impacts the rate of catalysis in the presence of these proton sources. The addition of Lewis acidic Sc3+ to Py2XPFe also results in an increase in current density of the CO2 reduction reaction. Resonance Raman as well as 1H-NMR spectroscopy indicates coordination to the pyridine substituents.
CRIS-Team Scopus Importer:2022-04-14
Keywords: CO; electrocatalysis; foot of the wave analysis; iron porphyrin; second coordination sphere